Low pump threshold CVD graphene based passively harmonic mode‐locked fibre laser - Kin Kee Chow (Electronics Letters)
A low pump threshold passively harmonic mode‐locked fibre laser is demonstrated. The key component is a chemical vapour deposition grown graphene saturable absorber to enable higher order harmonic mode‐locking (HML) of the fibre laser with good output noise characteristics. With a relatively low pump power of 100 mW, the fibre laser generates ∼1 ps soliton pulses at the 21st order of HML with 40 dB of super‐mode noise suppression.